Positron emission tomography in merkel cell carcinoma - Sachpekidis, Christos; Sidiropoulou, Polytimi; Hassel, Jessica C.; Drakoulis, Nikolaos; Dimitrakopoulou-Strauss, Antonia (Cancers, 2020)
Merkel cell carcinoma (MCC) is a rare neuroendocrine skin malignancy usually arising as a nonspecific nodule on sun-exposed areas of the head and neck. Given the poor prognosis of this aggressive tumor, assessment of disease burden in pre- and post-treatment care may ensure an optimal management with significant implications for patient surveillance and prognosis. Although imaging has established its role in locally advanced or distant metastatic MCC, a standard imaging algorithm is yet to be determined and respective recommendations are mainly based on melanoma. Positron emission tomography/computed tomography (PET/CT) is increasingly evolving as a valuable imaging tool in metastatic or unresectable MCC, mostly utilizing the glucose analogue 18F-fluorodeoxyglucose (18F-FDG) as a radiotracer. Despite being inferior in detecting the disease in its early stages compared to the “gold standard” of sentinel lymph node biopsy, recent evidence suggests an important role for 18F-FDG PET/CT in the routine workup of localized MCC. Moreover, 68Ga-labeled somatostatin analogues have been employed as PET tracers in the field of MCC with promising, yet comparable to 18F-FDG, results. This article provides a structured literature review of the most important studies investigating the role of PET or PET/CT in the clinical practice of MCC.
Gesehen am 24.11.2020